TMC151 Mandarin class - exposing students to some Chinese cultural practices / Hoe Foo Terng - Hoe, Foo Terng (Academy of Language Studies, 2025)
The Mandarin course textbook for Diploma students contains some brief notes on some Chinese cultural practices. These notes can be found in the first and third chapters. In the first chapter, an introduction to the second section of the 12th chapter of the Analects of Confucius - "Do not impose on others what you do not want others to do to you" is made. In addition to a brief introduction to the Analects of Confucius, other famous quotes in the Analects such as "When three people walk together, there will be someone who can teach me" are also explained to students.